Experimental Study of Wave Reflection on A-Jack Armor Unit on Seawall Structure - Sujantoko Sujantoko; Pramudya Adhi Pangestu; Widi Agus Pratikto; Mahmud Mustain; Wahyudi Wahyudi; Hasan Ikhwani (International Journal of Marine Engineering Innovation and Research, 2023)
In planning the construction of a seawall, it is necessary to consider several things, such as incoming waves, types of defensive units, and economic factors. So planning for the type and size of the armor unit used, it is expected that the structure will only experience minimal damage. In addition, there are other considerations, such as wave reflection by the structure. In the port area, a structure with low wave reflection is needed to keep the anchored pool calm. In this study, experimentally, the effect of the reflection coefficient on the seawall structure with the A-Jack armor unit was carried out. The experiment was held in a wave flume with regular waves with variations in height (0,10 – 0,175 cm) and periods (1,4 seconds and 1,6 seconds) of waves with three variations of a structural slope, namely 1:1, 1:1,5, and 1:2. The reflection coefficient analysis was carried out using the two-point methods which were recorded with a wave probe. Based on experiments, it is known that the steeper the slope of the structure will result in a more significant increase in reflection. To improve the accuracy of the spectral variations of the incident and reflected waves, it is necessary to record with three-wave probes because the two-wave probe method has several weaknesses and is prone to interference in analyzing the data obtained